ILLOCUTIONARY ACTS IN J.K. ROWLING’S “HARRY POTTER: THE CURSED CHILD” - Mustakim, Nur Fa'adillah; Weda, Sukardi (ELITERATE : Journal of English Linguistics and Literature Studies, 2022)
This article journal aims to accomplish two objectives. The first objective is to discover the types of illocutionary acts that are found in playscript "Harry Potter: The Cursed Child", and the second objective is to discover the functions of illocutionary acts that are found playscript "Harry Potter: The Cursed Child". This article journal used a qualitative method. This research also used theory about illocutionary acts by Searle and theory about the function of illocutionary acts by Leech. This research was only focused with utterance by the main character in this play script, Albus Severus Potter. The conclusions in this research are (1) four types of illocutionary acts that were used in play script, they were commissive, representative, expressive and directive. Among 67 illocutionary acts cases that utters by the main character in this play script, 22 cases were representative act, 9 cases were commissive act, 24 cases were directive act, and 12 cases were expressive act, (2) four types of functions of illocutionary acts that used in playscript, they were convivial, collaborative, conflictive, and competitive. Among 67 illocutionary acts uttered by the main character in this play script, 21 cases were collaborative, 24 cases were competitive function, 20 cases were convivial function and 2 cases were conflictive function.